position of the administration of US President Joseph Biden From the Iranian nuclear file (قضايا سياسية, 2023)
The administration of the current US President (Joe Biden) announced since the first week new policies towards the Iranian nuclear file, after that withdrawal from the nuclear agreement on May 8, 2018, which was announced by former US President (Donald Trump), unilaterally without coordination with its European allies, the United States of Europe, which is a member of the agreement, which gave Iran a justification to abandon its nuclear commitments within the framework of the Joint Comprehensive Plan of Action.Therefore, Joe Biden's administration is particularly important for achieving the new approach to U.S. relations with Iran, which is based on the need to expand the scope of the nuclear deal to add to it Iran's ballistic missile program and Iran's regional role. This is what Joe Biden sought, and his administration within the framework of international collective action in informal negotiations within the "5 + 1" group to discuss ways to activate the nuclear agreement again. Opening words: Nuclear, Joe Biden, Relations, Agreement.